Assessement of the Portuguese building thermal code: Newly revised requirements for cooling energy needs used to prevent the overheating of buildings in the summer - Panão, Marta Oliveira (2011)
In this paper, cooling energy needs are calculated by the steady-state methodology of the Portuguese building thermal code. After the first period of building code implementation, re-evaluation according to EN ISO 13790 is recommended in order to compare results with the dynamic simulation results. From these analyses, a newly revised methodology arises including a few corrections in procedure. This iterative result is sufficiently accurate to calculate the building’s cooling energy needs. Secondly, results show that the required conditions are insufficient to prevent overheating. The use of the gain utilization factor as an overheating risk index is suggested, according to an adaptive comfort protocol, and is integrated in the method used to calculate the maximum value for cooling energy needs. This proposed streamlined method depends on reference values: window-to-floor area ratio, window shading g-value, integrated solar radiation and gain utilization factor, which leads to threshold values significantly below the ones currently used. These revised requirements are more restrictive and, therefore, will act to improve a building’s thermal performance during summer. As a rule of thumb applied for Portuguese climates, the reference gain utilization factor should assume a minimum value of 0.8 for a latitude angle range of 40-41ºN, 0.6 for 38-39ºN and 0.5 for 37ºN.